#Fail: the quality and accuracy of nutrition-related information by influential Australian Instagram accounts - Emily Denniss; Rebecca Lindberg; Laura E. Marchese; Sarah A. McNaughton (BMC, 2024)
Abstract Background Social media is a popular source of information about food and nutrition. There is a high degree of inaccurate and poor-quality nutrition-related information present online. The aim of this study was to evaluate the quality and accuracy of nutrition-related information posted by popular Australian Instagram accounts and examine trends in quality and accuracy based on author, topic, post engagement, account verification and number of followers. Methods A sample of posts by Australian Instagram accounts with ≥ 100,000 followers who primarily posted about nutrition was collected between September 2020 and September 2021. Posts containing nutrition-related information were evaluated to determine the quality and accuracy of the information. Quality was assessed using the Principles for Health-Related Information on Social Media tool and accuracy was assessed against information contained in the Australian Dietary Guidelines, Practice-based Evidence in Nutrition database, Nutrient Reference Values and Metafact. Results A total of 676 posts were evaluated for quality and 510 posts for accuracy, originating from 47 Instagram accounts. Overall, 34.8% of posts were classified as being of poor quality, 59.2% mediocre, 6.1% good and no posts were of excellent quality. A total of 44.7% of posts contained inaccuracies. Posts authored by nutritionists or dietitians were associated with higher quality scores (β, 17.8, CI 13.94-21.65; P < 0.001) and higher accuracy scores (OR 4.69, CI 1.81-12.14, P = 0.001) compared to brands and other accounts. Information about supplements was of lower accuracy (OR 0.23, CI 0.10-0.51, P < 0.001) compared to information about weight loss and other nutrition topics. Engagement tended to be higher for posts of lower quality (β -0.59, P = 0.012), as did engagement rate (β -0.57, P = 0.016). There was no relationship between followers or account verification and information quality or accuracy and no relationship between engagement and accuracy. Conclusions Nutrition-related information published by influential Australian Instagram accounts is often inaccurate and of suboptimal quality. Information about supplements and posts by brand accounts is of the lowest quality and accuracy and information posted by nutritionists and dietitians is of a higher standard. Instagram users are at risk of being misinformed when engaging with Australian Instagram content for information about nutrition.